Literary Insights into Industrial and Frontier Societies: Comparative View on Cultural Poetics of the Donbas and Upper Silesia-Part I - Strzempa, Alina; Zabirko, Oleksandr (Sensus Historiae, 2025)
This article provides insight into the historical representations and literary constructions of two old industrial borderlands in Eastern and East-Central Europe: the Donbas and Upper Silesia. The first part addresses key questions about comparative studies, cultural poetics, regionalism, and the conflicts in both borderlands. It also explores the historical transformations that have shaped the regions in distinct ways, highlighting industrialization, the geopolitical composition of a borderland, and regionalism as common aspects for comparison. In the second part, two novels [The Length of Days. An Urban Ballad (2017) by Volodymyr Refeyenko (*1969) and East Wind (1932) by August Scholtis (1901–69)], stemming respectively from the Donbas and Upper Silesian historical conflicts, are presented in terms of the complex borderland narratives they embrace (biographies, plots, narrations, genres, and portrayals/literary representations). This article revolves around the research question of whether examining the outbreak of violence in Upper Silesia during 1919-22 can provide insights into the potential future trajectory of the Donbas.